Field-effect transistor antigen/antibody-TMDs sensors for the detection of COVID-19 samples. Issue 9 (10th February 2023) - Canton-Vitoria, Ruben; Sato, Kotaro; Motooka, Yashiro; Toyokuni, Shinya; Liu, Zheng; Kitaura, Ryo
Abstract : We demonstrate that covalent bonding between antibodies and TMDs results in hybrid materials that are remarkably stable. The most notable advantage is that the biosensor devices resist repeated washings without being damaged or losing sensitivity. Abstract : We fabricated sensors by modifying the surface of MoS2 and WS2 with COVID-19 antibodies and investigated their characteristics, including stability, reusability, sensitivity, and selectivity. Thiols and disulfanes in antibodies strongly interact with vacant Mo or W sites of MoS2 or WS2, yielding durable devices that are stable for several days in the air or water. More importantly, detachment of the antibodies is suppressed even during the aggressive cleaning process of the devices at pH 3, which allows reusing the same device in several experiments without appreciable loss of sensitivity. Therefore, the nanodevice may be employed in samples of different patients. Further, we found a limit of detection (LOD) of 1 fg ml −1 at room temperature, time responses of 1 second, and selectivity against interferences such as KLH protein or Albumin.